Mechanical force modulates inflammation and immunomodulation in periodontal ligament cells - Chansaenroj Jira; Suwittayarak Ravipha; Egusa Hiroshi; Samaranayake Lakshman P.; Osathanon Thanaphum (Medical Review)
Mechanical forces control a multitude of biological responses in various cells and tissues. The periodontal ligament, located between the tooth’s root and alveolar bone, is a major tissue compartment that is incessantly subjected to such mechanical stimulation through either normal or abnormal oral functionality. It is now known that mechanical stimulation activates periodontal ligament stem cells (PDLSCs) to modulate periodontal immunity and regulate inflammation – a basic feature of periodontal disease that affects virtually every human during their lifetime. For instance, shear stress induces the expression of immunomodulatory-related gene, indoleamine 2,3-dioxygenase (IDO). IDO cleaves l-tryptophan, resulting in increased l-kynurenine levels that, in turn, further promote regulatory T-cell differentiation and inhibit T cell proliferation. These and other related data reinforce the notion that mechanical stimulation plays a crucial role in controlling inflammation and immunomodulation of periodontal tissues. Further investigations, however, are warranted to evaluate the immunomodulatory features of PDLSCs so as to understand the pathological basis of periodontal disease and translate these into clinical interventions.